If the worst comes to the worst: Dictator giving when recipients endowments are risky - Christoph Engel; Sebastian J. Goerg (Max Planck Institute for Research on Collective Goods, 2015)
Donors may often not be sure whether a recipient really deserves their help. Does this uncertainty deter generosity? In an experiment we find that, to the contrary, under most specifications of uncertainty, dictators give more, compared with the donation the same dictator makes to a recipient they know to have the expected value of the endowment with certainty. They are particularly concerned about the possibility that a recipient leaves the lab with no payoff from the game.
Keywords: D81; C91; D03; 330; dictator game; uncertainty; donation